Comparison of NucliSens and Amplicor Monitor Assays for Quantification of Human Immunodeficiency Virus Type 1 (HIV-1) RNA in Plasma of Persons with HIV-1 Subtype A Infection in Abidjan, Côte d’Ivoire - Nkengasong, John N. (American Society for Microbiology, 1998)
We compared the sensitivity and accuracy of the NucliSens assay and those of both the standard and modified (addition of a new primer set, primer mix 1, supplied by Roche) Amplicor HIV Monitor assays to quantify human immunodeficiency virus type 1 (HIV-1) RNA in persons infected with HIV-1 subtype A in Abidjan, Côte d’Ivoire. Seventy-one plasma samples from HIV-1-seropositive persons at different stages of HIV infection and 15 samples from HIV antibody-negative persons were analyzed. The HIV-1 genetic subtype was determined either by DNA sequencing or by a restriction fragment length polymorphism assay. Of the 71 samples, 70 (98%) were subtype A and 1 was subtype G. Of the 70 subtype A samples, the proportion of RNA-positive plasma samples and mean HIV-1 RNA levels were significantly higher by the modified HIV Monitor assay (n = 67 [96%]; mean RNA levels, 5.2 log(10) HIV-1 RNA copies/ml) than the NucliSens assay (n = 56 [80%]; 4.3 log(10) HIV-1 RNA copies/ml) or the standard HIV Monitor assay (n = 44 [63%]; mean RNA levels, 3.8 log(10) HIV-1 RNA copies/ml) (all P values were <0.05). The HIV-1 RNA levels by the modified HIV Monitor assay correlated significantly with those by the NucliSens assay (r = 0.76; P < 0.001) and the standard HIV Monitor assay (r = 0.57; P < 0.001), as did the RNA levels by the NucliSens and the standard HIV Monitor assays (r = 0.60; P < 0.001). Lower CD4 cell counts were significantly correlated with higher HIV-1 RNA levels by all three assays (r = −0.47 for the NucliSens assay, −0.45 for the standard HIV Monitor assay, and −0.62 for the modified HIV Monitor assay). These results indicate that the modified HIV Monitor assay has the highest sensitivity and efficiency at quantifying the levels of RNA in persons infected with HIV-1 subtype A and thus constitutes a valuable tool for the monitoring of RNA levels in areas of Africa were HIV-1 subtype A is predominant.